TINGKAT PARTISIPASI PETANI WORTEL DALAM KELOMPOK TANI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI KASUS DI DESA LINGGA KECAMATAN SIMPANG EMPAT KABUPATEN KARO) - Pakpahan, Helena T. (Berkala Ilmiah AGRIDEVINA, 2017)
Agriculture as a central point of development in increasing social welfare, with the effortto increase agricultural product and should be based on existence of effort to affectfarmers. The farmers should be educated, guided, encouraged to join a team so theinteraction among the farmers occured. The aims of this research are to measure  theparticipation level of carrot farmers in farming team, the characteristic relations offarmers social economy with the participation level of farmers. The participation levelwas analized by sums up and scoring the data were found and the characteristic relationsof farmers social economy with the participation level of farmers was analized by usingRank Spearmen correlation. The final research showed that the participation level offarmers in farming team including in high category with the score was 12.03. In partial,there was real relations found between the education level, the frequency in followingobservation, and the amount of obligation with the participation level in farming teamwhile the age, farming experience, farm land width, and product which did not have realrelations with the participation level.